Unprecedented suppression of Panama’s Pacific upwelling in 2025 - Aaron O’Dea; Andrew J. Sellers; Carmen Pérez-Medina; Javier Pardo Díaz; Alexandra Guzmán Bloise; Christopher Pöhlker; Michał T. Chiliński; Hedy M. Aardema; Jonathan D. Cybulski; Lena Heins; Steven R. Paton; Hans A. Slagter; et al. (Proceedings of the National Academy of Sciences, 2025)
The Gulf of Panama’s (GOP) seasonal upwelling system has consistently delivered cool, nutrient-rich waters via northerly trade winds every January–April for at least 40 y. Here, we document the failure of this normally highly predictable phenomenon in 2025. Data suggest that the cause was a reduction in Panama wind-jet frequency, duration, and strength, possibly related to the Intertropical Convergence Zone (ITCZ) position during the 2024–2025 La Niña, though the mechanisms remain unclear. Nevertheless, the consequences are likely significant, including decreases in fisheries productivity and exacerbated thermal stress on corals that typically benefit from upwelling’s cooling. This event underscores how climate disruption can threaten wind-driven tropical upwelling systems, which remain poorly monitored and studied despite their importance to ecology and coastal economies.